1981
DOI: 10.1063/1.92691
|View full text |Cite
|
Sign up to set email alerts
|

High concentration antimony diffusion into silicon using auxiliary wafers

Abstract: The behavior of auxiliary wafers used for Sb diffusion has been studied, with the auxiliary wafers set face to face with diffusion wafers. A high Sb concentration, as high as the solid solubility of Sb into silicon, was attained by auxiliary wafers lapped with alumina powder but not attained by those lapped with carborundum powder. Sapphire substrates, chemical vapor deposition-Al2O3 film deposited on silicon wafers, and Al+ -implanted silicon wafers were used for the auxiliary wafers, and they brought desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Results described above are too complex to discuss briefly. A similar phenomenon is not seen anywhere but in oar reports (6,9).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Results described above are too complex to discuss briefly. A similar phenomenon is not seen anywhere but in oar reports (6,9).…”
Section: Discussionsupporting
confidence: 58%
“…A previous paper (9) reported that comparison of the Sb concentration at the silicon surface Co with the Sb concentration at glass-silicon interface Cr for elemental Sb produced good results. Therefore, it was concluded that carrier concentration in silicon depended on the concentration of elemental Sb at the glass-silicon interface.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations